Geospatial Analysis of Nonmarket Values to Prioritize Forest Restoration - Adrienne B. Soder; Julie M. Mueller; Abraham E. Springer; Katelyn E. LaPine (Land, 2022)
Forest restoration is necessary for maintaining healthy watersheds and the ecological spatial networks that provide environmental goods and services. Consideration of the dollar value of these provided benefits in restoration planning is essential to the efficient use of limited resources available to project implementation. Nonmarket valuation is a methodology of economics commonly used to estimate monetary values for environmental goods and services that are not typically bought or sold in a traditional market. Valuation studies are prolific within the restoration literature; however, the use of nonmarket values as decision support is not well represented. We introduce a method using Geographic Information Systems (GIS) to spatially analyze the results from a nonmarket valuation study that estimated dollar values for the attributes of forest restoration characteristic of a semi-arid watershed in the Southwest United States. Map layers were created for the five attributes valued by the study and represent areas in the watershed that are designated as critical habitats, determined to influence surface water quality, prone to high-severity wildfire, representative of culturally significant areas, and contribute to aquifer recharge. A series of overlay analyses were performed to create a composite benefit map that spatially displays nonmarket values throughout the watershed. The per acre benefit values range from USD 0 to USD 104 where all five attributes are present.